The risk of contracting infectious diseases in public swimming pools: a review - Zsófia Barna (Annali dell'Istituto Superiore di Sanità, 2012)
A review of pathogenic microorganisms presenting risk of infection in pool based artificial recreational water venues is extracted from the available scientific literature. The microorganisms are grouped both according to their way of spread and their survival and growth strategies and their characteristics relevant for the pool and spa based recreation are discussed. In order to put the proposed risks on a solid basis, among others a ten year excerpt of the waterborne disease statistics of the Centers for Disease Control and Prevention (CDC) is used throughout the article.